Double-layer anti-oxidation coating on niobium alloy surface and preparation method of double-layer anti-oxidation coating

By preparing Si-Cr-Ti-Al inner coating and MoSi2-Al-SiC outer coating on the surface of the niobium alloy, the problem of poor oxidation performance of niobium alloy in high temperature environment is solved, and long-term resistance above 1700℃ is achieved Improved oxidation performance.

CN119243140AActive Publication Date: 2025-01-03XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY

Patent Information

Application Number
CN202411355629.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

Niobium alloy has poor oxidation performance under high temperature environments, and the existing single Si-Cr-Ti coating cannot meet the long-term use needs at an environment above 1500°C.

Method used

Using the double-layer antioxidant coating method, Si-Cr-Ti-Al inner coating and MoSi2-Al-SiC outer coating were prepared first, and the composite coating was formed by spraying and high-energy ball mill mixing slurry combined with vacuum sintering technology. To improve antioxidant properties.

Benefits of technology

The high-temperature oxidation performance of niobium alloy is significantly improved. The double-layer antioxidant coating on the surface of niobium alloy has a static antioxidant life of more than 15 hours in air at 1700℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243140A_ABST
    Figure CN119243140A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal coating preparation, and particularly relates to a double-layer anti-oxidation coating on the niobium alloy surface and a preparation method thereof.A Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating are sequentially prepared on the niobium alloy surface, SiC in the outer coating serves as a reinforcement, and meanwhile Al and MoSi2 can form a continuous Al2O3 and SiO2 protective film; the inner coating serves as a middle layer, Cr, Si, Ti and Al in the inner coating make contact with permeated oxygen, generated Cr2O3, SiO2, TiO2 and Al2O3 can greatly reduce the oxygen permeability and improve the oxidation resistance of the coating, and the composite coating remarkably improves the high-temperature oxidation resistance of niobium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal coating preparation, and specifically relates to a double-layer anti-oxidation coating on the surface of a niobium alloy and a preparation method thereof. Background Art

[0002] Niobium alloy has high melting point, high hardness, excellent mechanical properties and corrosion resistance, etc., and has been widely used in the fields of nuclear industry and aerospace. However, due to the low initial oxidation temperature of niobium alloy, severe oxidation will occur at 600°C, and it has poor oxidation resistance. Therefore, oxide, aluminide or silicide coatings are usually prepared on the surface of niobium alloy to improve its oxidation resistance to meet the development needs of modern aerospace technology and other fields. Current research shows that the Si-Cr-Ti coating prepared on the surface of niobium alloy can achieve good stability in static air at 1400°C, but when the service temperature reaches 1500°C or even higher, the single coating cannot meet the long-term use in this environment. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a double-layer anti-oxidation coating on the surface of a niobium alloy and a preparation method thereof.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0006] S1. Use sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0007] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, and then drying them for standby use;

[0008] S3, mixing the Si powder, Cr powder, Ti powder and Al powder processed in step S2 in a certain proportion, mixing the MoSi2 powder, Al powder and SiC powder processed in step S2 in a certain proportion, adding appropriate amounts of diluent and binder respectively, and mixing them with a high-energy planetary ball mill to prepare a uniform slurry for standby use;

[0009] S4, preparing a Si-Cr-Ti-Al slurry coating on the surface of the niobium alloy treated in step S1 by spraying, drying naturally and in a vacuum furnace, and then sintering in a vacuum sintering furnace to obtain a Si-Cr-Ti-Al inner coating for standby use;

[0010] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, which is then dried naturally and in a vacuum furnace, and then sintered in a vacuum sintering furnace to obtain a MoSi2-Al-SiC outer coating.

[0011] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, in step S2, the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder and SiC powder after preliminary grinding treatment is 10 to 40 μm.

[0012] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, in said step S3, the ball-to-material ratio of ball milling is 20:1, the rotation speed is 300 r / min, the mixing time of ball milling is 24 h, wherein the forward and reverse rotations are 12 h each.

[0013] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to the present invention, in step S3, the mass ratio of Si powder, Cr powder, Ti powder and Al powder is (30-50):(10-30):15:15.

[0014] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, in step S3, the mass ratio of MoSi2 powder, Al powder and SiC powder is (70-80):(5-30):5.

[0015] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to the present invention, in step S3, the binder is polyvinyl butyral and the diluent is anhydrous ethanol.

[0016] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to the present invention, wherein: in the steps S4 and S5, the natural drying time is 2 days.

[0017] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, in the steps S4 and S5, the vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h.

[0018] As a preferred embodiment of the method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, in said steps S4 and S5, during sintering, the temperature is increased from 400°C to a sintering holding temperature of 1570°C at a heating rate of 10°C / min and kept at that temperature for 0.5h.

[0019] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0020] A double-layer anti-oxidation coating on the surface of a niobium alloy is prepared by adopting the preparation method of the double-layer anti-oxidation coating on the surface of a niobium alloy.

[0021] As a preferred embodiment of the double-layer anti-oxidation coating on the surface of a niobium alloy described in the present invention, the double-layer anti-oxidation coating on the surface of the niobium alloy comprises a Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating, the thickness of the Si-Cr-Ti-Al inner coating is 10 to 100 μm, the thickness of the MoSi2-Al-SiC outer coating is 15 to 110 μm, and the static anti-oxidation life of the double-layer anti-oxidation coating on the surface of the niobium alloy in air at 1700°C is more than 15 hours.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention provides a double-layer anti-oxidation coating on the surface of a niobium alloy and a preparation method thereof. A Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating are sequentially prepared on the surface of the niobium alloy. The SiC in the outer coating acts as a reinforcement, and Al and MoSi2 form relatively continuous Al2O3 and SiO2 protective films. The inner coating acts as an intermediate layer, and Cr, Si, Ti and Al in the inner coating contact with the infiltrated oxygen. The generated Cr2O3, SiO2, TiO2 and Al2O3 can greatly reduce the oxygen permeability and improve the anti-oxidation ability of the coating. The composite coating significantly improves the resistance of the niobium alloy to high-temperature oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0025] Figure 1 Surface and cross-sectional SEM images of Example 1 of the present invention.

[0026] Figure 2 Surface and cross-sectional SEM images of Comparative Example 1 of the present invention.

[0027] Figure 3 Surface and cross-sectional SEM images of Comparative Example 2 of the present invention.

[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0029] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a double-layer anti-oxidation coating on the surface of a niobium alloy and a preparation method thereof. A Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating are sequentially prepared on the surface of the niobium alloy, which exhibits relatively good anti-oxidation performance. The double-layer anti-oxidation coating on the surface of the niobium alloy has a static anti-oxidation life of more than 15 hours in air at 1700°C.

[0031] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0032] Example 1

[0033] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0034] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0035] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0036] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 35wt%, the content of Cr powder is 25wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 8wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 70wt%, the content of Al powder is 18wt%, and the content of SiC powder is 5wt%; 5wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0037] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. Drying in a vacuum furnace by a step-by-step heating method, keeping at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping at 100°C for 1.0h; then sending into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and keeping for 0.5h, to obtain a Si-Cr-Ti-Al inner coating with a thickness of 80μm, which is set aside;

[0038] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum dried in sequence. The natural drying time is 2 days. The vacuum drying adopts a step-by-step heating method, keeping warm at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping warm at 100°C for 1.0h; then the sample is sent to a vacuum sintering furnace for sintering. During sintering, the temperature is increased from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept warm for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 100μm.

[0039] The surface and cross-sectional SEM images of the double-layer anti-oxidation coating on the niobium alloy surface prepared in this embodiment are shown in FIG. Figure 1 As shown (the left side is the surface SEM image, and the right side is the cross-sectional SEM image), the coating surface is relatively smooth and no obvious cracks are found; the inner coating and the outer coating have a good bonding effect, and the interior of the coating is dense and uniform.

[0040] Example 2

[0041] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0042] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0043] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0044] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 35wt%, the content of Cr powder is 28wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 5wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 70wt%, the content of Al powder is 20wt%, and the content of SiC powder is 5wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0045] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days, and drying in a vacuum furnace by a step-by-step heating method, keeping at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping at 100°C for 1.0h; then sending into a vacuum sintering furnace for sintering, heating from 400°C to sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping for 0.5h, to obtain Si-Cr-Ti-Al inner coating with a thickness of 30μm, for standby use;

[0046] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum-dried in sequence. The natural drying time is 2 days. The vacuum-dried sample is dried by a step-by-step heating method, and is kept at 40°C for 0.5h, then heated to 65°C for 0.5h, and finally kept at 100°C for 1.0h. The sample is then sent to a vacuum sintering furnace for sintering. During sintering, the sample is heated from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 50μm.

[0047] Example 3

[0048] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0049] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0050] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0051] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 35wt%, the content of Cr powder is 30wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 70wt%, the content of Al powder is 20wt%, and the content of SiC powder is 5wt%; 1wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0052] S4, using a spraying method to prepare a Si-Cr-Ti-Al slurry coating on the surface of the niobium alloy treated in step S1, and then drying it naturally and in a vacuum furnace for 2 days. The vacuum furnace is dried by a step-by-step heating method, keeping it at 40°C for 0.5h, then heating it to 65°C for 0.5h, and finally keeping it at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating it from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping it for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 10μm, which is used for standby;

[0053] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum dried in sequence. The natural drying time is 2 days. The vacuum drying adopts a step-by-step heating method, keeping warm at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping warm at 100°C for 1.0h; then it is sent to a vacuum sintering furnace for sintering. During sintering, the temperature is increased from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept warm for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 20μm.

[0054] Example 4

[0055] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0056] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0057] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0058] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 35wt%, the content of Cr powder is 33wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 1wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 75wt%, the content of Al powder is 15wt%, and the content of SiC powder is 5wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0059] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. The vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping the temperature for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 25μm, which is used for standby;

[0060] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum dried in sequence. The natural drying time is 2 days. The vacuum drying adopts a step-by-step heating method, keeping warm at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping warm at 100°C for 1.0h; then it is sent to a vacuum sintering furnace for sintering. During sintering, the temperature is increased from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept warm for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 75μm.

[0061] Example 5

[0062] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0063] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0064] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0065] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 40wt%, the content of Cr powder is 25wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 80wt%, the content of Al powder is 5wt%, and the content of SiC powder is 5wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0066] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. The vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping the temperature for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 55μm, which is used for standby;

[0067] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum dried in sequence. The natural drying time is 2 days. The vacuum drying adopts a step-by-step heating method, keeping warm at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping warm at 100°C for 1.0h; then it is sent to a vacuum sintering furnace for sintering. During sintering, the temperature is increased from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept warm for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 15μm.

[0068] Example 6

[0069] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0070] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0071] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0072] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 45wt%, the content of Cr powder is 20wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 80wt%, the content of Al powder is 10wt%, and the content of SiC powder is 5wt%; 1wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0073] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. The vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping the temperature for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 100μm, which is used for standby;

[0074] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum-dried in sequence. The natural drying time is 2 days. The vacuum-dried sample is dried by a step-by-step heating method, and is kept at 40°C for 0.5h, then heated to 65°C for 0.5h, and finally kept at 100°C for 1.0h. The sample is then sent to a vacuum sintering furnace for sintering. During sintering, the sample is heated from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 50μm.

[0075] Example 7

[0076] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0077] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0078] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0079] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of Si powder is 50wt%, the content of Cr powder is 15wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 3wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and a proper amount of diluent and binder are added, wherein: the content of MoSi2 powder is 80wt%, the content of Al powder is 10wt%, and the content of SiC powder is 5wt%; 2.5wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0080] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. The vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping the temperature for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 45μm, which is used for standby;

[0081] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum-dried in sequence. The natural drying time is 2 days. The vacuum-dried sample is dried by a step-by-step heating method, and is kept at 40°C for 0.5h, then heated to 65°C for 0.5h, and finally kept at 100°C for 1.0h. The sample is then sent to a vacuum sintering furnace for sintering. During sintering, the temperature is increased from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 110 μm.

[0082] Example 8

[0083] A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy comprises the following steps:

[0084] S1. Use 200-2000# sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use;

[0085] S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, wherein the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder after preliminary grinding treatment is 10 to 40 μm, and then drying and standby;

[0086] S3, the Si powder, Cr powder, Ti powder, Al powder treated in step S2 are mixed in a certain proportion, and appropriate diluent and binder are added, wherein: the content of Si powder is 45wt%, the content of Cr powder is 15wt%, the content of Ti powder is 15wt%, and the content of Al powder is 15wt%; 5wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; the MoSi2 powder, Al powder, and SiC powder treated in step S2 are mixed in a certain proportion, and appropriate diluent and binder are added, wherein: the content of MoSi2 powder is 80wt%, the content of Al powder is 10wt%, and the content of SiC powder is 5wt%; 3.5wt% polyvinyl butyral is added, and the rest is anhydrous ethanol; respectively, they are mixed with a high-energy planetary ball mill, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300r / min, the mixing time of the ball mill is 24h, wherein the forward and reverse rotations are 12h each; a uniform slurry is prepared for standby use;

[0087] S4, preparing Si-Cr-Ti-Al slurry coating on the surface of niobium alloy treated in step S1 by spraying, and then drying naturally and in a vacuum furnace for 2 days. The vacuum furnace drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h; then sending it into a vacuum sintering furnace for sintering, heating from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min during sintering, and keeping the temperature for 0.5h to obtain a Si-Cr-Ti-Al inner coating with a thickness of 50μm, which is used for standby;

[0088] S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, and then naturally dried and vacuum-dried in sequence. The natural drying time is 2 days. The vacuum-dried sample is dried by a step-by-step heating method, and is kept at 40°C for 0.5h, then heated to 65°C for 0.5h, and finally kept at 100°C for 1.0h. The sample is then sent to a vacuum sintering furnace for sintering. During sintering, the sample is heated from 400°C to a sintering insulation temperature of 1570°C at a heating rate of 10°C / min, and kept for 0.5h to obtain a MoSi2-Al-SiC outer coating with a thickness of 50μm.

[0089] Comparative Example 1

[0090] The difference from Example 1 is that only the Si—Cr—Ti—Al coating is prepared.

[0091] The surface and cross-sectional SEM images of the coating on the niobium alloy surface prepared in this comparative example are as follows: Figure 2 As shown (the left side is the surface SEM image, and the right side is the cross-sectional SEM image), the single Si-Cr-Ti-Al coating has no cracks on the surface and is relatively smooth; the coating is well bonded to the substrate and the interior of the coating is relatively dense.

[0092] Comparative Example 2

[0093] The difference from Example 1 is that only the MoSi2-Al-SiC coating is prepared.

[0094] The surface and cross-sectional SEM images of the coating on the niobium alloy surface prepared in this comparative example are as follows: Figure 3 As shown (the left side is the surface SEM image, and the right side is the cross-sectional SEM image), the surface of the single MoSi2-Al-SiC coating is relatively smooth, crack-free, and relatively dense; the coating and the substrate are well bonded.

[0095] The niobium alloys with coatings on the surfaces prepared in the above embodiments and comparative examples were subjected to a static oxidation resistance test in air at 1700°C. The test was conducted with a holding time of 10 to 20 hours in a gradient of 1 hour. The integrity of the coating after oxidation and the presence of cracks were used as a basis for judging the oxidation resistance life. The results are shown in the following table. It can be seen that the oxidation resistance life of the double-layer oxidation resistance coating on the surface of the niobium alloy of the present invention is ≥15 hours, and the oxidation resistance life of the single coating is ≤13 hours.

[0096] Antioxidant life (h) Example 1 16h Example 2 16h Example 3 17h Example 4 15h Example 5 18h Example 6 15h Example 7 20h Example 8 19h Comparative Example 1 13h Comparative Example 2 11h

[0097] It can be seen from the above embodiments and comparative examples that the present invention sequentially prepares a Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating on the surface of the niobium alloy, wherein the SiC in the outer coating acts as a reinforcement, and Al and MoSi2 simultaneously form relatively continuous Al2O3 and SiO2 protective films; the inner coating acts as an intermediate layer, wherein Cr, Si, Ti and Al are in contact with the infiltrated oxygen, and the generated Cr2O3, SiO2, TiO2 and Al2O3 can greatly reduce the oxygen permeability and improve the oxidation resistance of the coating, and this composite coating significantly improves the resistance of the niobium alloy to high-temperature oxidation.

[0098] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy, characterized in that: The steps include: S1. Use sandpaper to roughly grind the surface of the niobium alloy, then rinse with clean water, then use alkaline solution, pickling solution and anhydrous ethanol for ultrasonic cleaning in sequence, and finally blow dry for standby use; S2, using a planetary ball mill to perform preliminary grinding treatment on Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder, and SiC powder, and then drying them for standby use; S3, mixing the Si powder, Cr powder, Ti powder and Al powder processed in step S2 in a certain proportion, mixing the MoSi2 powder, Al powder and SiC powder processed in step S2 in a certain proportion, adding appropriate amounts of diluent and binder respectively, and mixing them with a high-energy planetary ball mill to prepare a uniform slurry for standby use; S4, preparing a Si-Cr-Ti-Al slurry coating on the surface of the niobium alloy treated in step S1 by spraying, drying naturally and in a vacuum furnace, and then sintering in a vacuum sintering furnace to obtain a Si-Cr-Ti-Al inner coating for standby use; S5. The sample processed in step S4 is sprayed to prepare a MoSi2-Al-SiC slurry coating, which is then dried naturally and in a vacuum furnace, and then sintered in a vacuum sintering furnace to obtain a MoSi2-Al-SiC outer coating.

2. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In the step S2, the particle size of the Si powder, Cr powder, Ti powder, Al powder, MoSi2 powder and SiC powder after preliminary grinding is 10 to 40 μm.

3. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In step S3, the ball-to-material ratio of the ball mill is 20:1, the rotation speed is 300 r / min, and the mixing time of the ball mill is 24 hours, including 12 hours for each forward and reverse rotation.

4. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In the step S3, the mass ratio of Si powder, Cr powder, Ti powder and Al powder is (30-50):(10-30):15:

15.

5. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In step S3, the mass ratio of MoSi2 powder, Al powder and SiC powder is (70-80):(5-30):

5.

6. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In the step S3, the binder is polyvinyl butyral and the diluent is anhydrous ethanol.

7. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In the steps S4 and S5, the natural drying time is 2 days; the vacuum oven drying adopts a step-by-step heating method, keeping the temperature at 40°C for 0.5h, then heating to 65°C for 0.5h, and finally keeping the temperature at 100°C for 1.0h.

8. The method for preparing a double-layer anti-oxidation coating on the surface of a niobium alloy according to claim 1, characterized in that: In the steps S4 and S5, during sintering, the temperature is increased from 400° C. to a sintering holding temperature of 1570° C. at a heating rate of 10° C. / min, and the temperature is kept for 0.5 h.

9. A double-layer anti-oxidation coating on the surface of a niobium alloy, characterized in that: The double-layer anti-oxidation coating on the surface of the niobium alloy is prepared by the preparation method of any one of claims 1 to 8.

10. The double-layer anti-oxidation coating on the surface of niobium alloy according to claim 9, characterized in that: The double-layer anti-oxidation coating on the surface of the niobium alloy comprises a Si-Cr-Ti-Al inner coating and a MoSi2-Al-SiC outer coating, the thickness of the Si-Cr-Ti-Al inner coating is 10 to 100 μm, the thickness of the MoSi2-Al-SiC outer coating is 15 to 110 μm, and the static anti-oxidation life of the double-layer anti-oxidation coating on the surface of the niobium alloy in air at 1700° C. is more than 15 hours.

Citation Information

Patent Citations

  • Niobic alloy high temperature antioxidation silicide coating and preparation method thereof

    CN101200801A

  • High-temperature oxidation resistant coating on niobium alloy surface and preparation method of high-temperature oxidation resistant coating

    CN104561882A

  • Niobium alloy surface high-temperature abrasion resisting coating and preparation method thereof

    CN106435460A

  • High-temperature anti-oxidization niobium alloy surface composite silicide coating and preparing method

    CN107190261A

  • Preparation method of MoSi2 coating on surface of niobium alloy

    CN109913870A

Cited By

  • Multi-layer complex-phase composite silicide high-temperature coating and preparation method thereof

    CN119932469A